Non-paretic lower limb muscle wasting during acute phase is associated with dependent ambulation in patients with stroke. (April 2020) - Nozoe, Masafumi; Kanai, Masashi; Kubo, Hiroki; Yamamoto, Miho; Shimada, Shinichi; Mase, Kyoshi
Highlights: We examined whether lower limb muscle wasting during the acute phase is associated with the dependent ambulation status. There were significant decreases of quadriceps muscle thickness in the non-paretic limb for non-ambulatory patients than ambulatory patients. Muscle wasting in the non-paretic limb was a significant independent predictor of dependent ambulation in stroke patients. Abstract: Background: Muscle wasting in patients with stroke is a factor for a poor functional outcome. However, there have been few studies on the relationships between lower limb muscle wasting during the acute phase and dependent ambulation. This study examined whether lower limb muscle wasting during the acute phase is associated with the dependent ambulation status at 3 months after stroke. Methods: In this observational cohort study, we measured the quadriceps muscle thickness in the paretic and non-paretic limbs within 1 and 3 weeks after admission using ultrasonography in non-ambulatory patients with acute stroke. Patients were categorized into two groups based on their ambulation ability: dependent, functional ambulation category (FAC) 0–3 and independent, FAC 4–5) at 3 months after stroke. Results: In total, 55 patients were included and completed follow-up, and 28 patients (51%) had an ambulation status of dependent at 3 months after stroke. Significant differences in muscle wasting were observed in the non-paretic limb (−5.5% [8.7%] : −16.8% [13.6%], independent group: dependent group, respectively, P < 0.001), but not in the paretic limb (−15.0% [14.3%] : −18.7% [15.1%], P = 0.36). Even after adjusting for covariates, muscle wasting in the non-paretic limb was a significant independent predictor of dependent ambulation (adjusted odds ratio, 0.87; 95% confidence interval, 0.76–0.99, P = 0.033). Conclusion: Post-stroke muscle wasting in the non-paretic lower limb during the acute phase is independently associated with dependent ambulation after stroke.